2017
DOI: 10.1093/ofid/ofx222
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Human Pegivirus on CD4 Cell Count in HIV-Positive Persons in Botswana

Abstract: BackgroundHuman pegiviruses (HPgV)—formerly known as hepatitis G virus or GB virus C (GBV-C)—are common single-stranded RNA viruses that may have a beneficial impact on slowing HIV disease progression. The data on HPgV in resource-limited regions such as Sub-Saharan Africa are scarce. Thus, we conducted the first study of HPgV in Botswana as part of a natural history study of HIV subtype C disease progression.MethodsPlasma samples from 133 HIV-positive adults were evaluated for HPgV RNA, and the 5’UTR was sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The median HIV-1 viral load in those infected with HPgV-1 subtype 2b was significantly lower, as were the higher CD4+ T-cell counts. The fact that some HPgV-1 strains influence the clinical course of HIV-1 infection more than others has already been suggested [19, 3133]. Subtype 2b and genotype 5 were already related to higher rates of CD4+ T-cells compared to subtype 2a and genotype 1 [19, 33], and genotype 7 has already been associated with slower progression to AIDS [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The median HIV-1 viral load in those infected with HPgV-1 subtype 2b was significantly lower, as were the higher CD4+ T-cell counts. The fact that some HPgV-1 strains influence the clinical course of HIV-1 infection more than others has already been suggested [19, 3133]. Subtype 2b and genotype 5 were already related to higher rates of CD4+ T-cells compared to subtype 2a and genotype 1 [19, 33], and genotype 7 has already been associated with slower progression to AIDS [34].…”
Section: Discussionmentioning
confidence: 99%
“…The fact that some HPgV-1 strains influence the clinical course of HIV-1 infection more than others has already been suggested [19, 3133]. Subtype 2b and genotype 5 were already related to higher rates of CD4+ T-cells compared to subtype 2a and genotype 1 [19, 33], and genotype 7 has already been associated with slower progression to AIDS [34]. It is thought that the different HPgV-1 genotypes have different tropisms to the CXCR4 and CCR5 coreceptors used by HIV-1 for entry into host cells, which would be determinant in the evolution of HIV-1 infection [35].…”
Section: Discussionmentioning
confidence: 99%
“…Viral RNA was extracted using the QIAmp Ultrasens Virus Kit (for DNA and RNA) (QIAGEN, Valencia, CA). As described previously (2123), HPgV RNA was detected by amplification of the 5′ untranslated region (UTR) with the antisense primer 5′ – ATG CCA CCC GCC CTC ACC CGA A – 3′ (nucleotides [nt] 494-473 according to GenBank accession number AY196904) and the sense primer 5′ – AAA GGT GGT GGA TGG GTG ATG – 3′ (nt 67-87) via OneStep RT-PCR (QIAGEN). Amplification conditions were 50°C for 59 min, 10 min at 94°C, then 35 cycles of 30 s at 94°C, 1 min at 55°C, and 1 min at 72°C, followed by 20 min at 72°C.…”
Section: Methodsmentioning
confidence: 99%
“…13,16,17,18 Beneficial effects of HPgV viremia on HIV disease progression was explored by several groups and found higher CD4 cell counts, lower HIV viral loads and longer AIDs-free survival times for individuals with HPgV infection. [19][20][21][22] However, other studies have contradicted these findings and observed no beneficial effects of HPgV infection in individuals living with HIV. 23,24,25 Tucker et al reported that HPgV has worldwide distribution and is found in the general population.…”
Section: Introductionmentioning
confidence: 98%